2001
DOI: 10.1046/j.1469-0705.2001.abs05-4.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cervical length with ultrasound: evaluation of the procedures and duration of a learning method

Abstract: Objectives: To relate preoperative cervical length, operative findings, postoperative cervical length and pregnancy outcome in high risk women treated with ultrasound indicated cervical cerclage to establish if it was possible to determine the most appropriate criteria to offer cervical cerclage. Study design: A prospective observational study of 305 high risk women undergoing serial transvaginal ultrasonographic assessment of cervical length during the second trimester. Fifty-four women met criteria for cercl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…In our data, we obtained strong coefficients of intra and interobserver correlation, the same as Valentin and Burger,18,19 it is demonstrated that these agreements increase with training. 20 However, the Bishop score suffers from great subjectivity and its reproducibility is minor. 6 In any case, the Bishop score is inherent to the induction and should remain in our practice.…”
Section: Labor Induction B Bueno Et Almentioning
confidence: 99%
“…In our data, we obtained strong coefficients of intra and interobserver correlation, the same as Valentin and Burger,18,19 it is demonstrated that these agreements increase with training. 20 However, the Bishop score suffers from great subjectivity and its reproducibility is minor. 6 In any case, the Bishop score is inherent to the induction and should remain in our practice.…”
Section: Labor Induction B Bueno Et Almentioning
confidence: 99%
“…First, the variability of the technique has limited the standardisation of measurements. Second, there is a clear need of training for measurement of the cervix by transvaginal ultrasound (8). Finally, and most importantly in our culture, many patients are not happy to undergo TVS.…”
Section: Discussionmentioning
confidence: 99%
“…La variabilité inter-et intraobservateur de l'échographie est inférieure à 10 % aux mains d'opéra-teurs entraînés. Aussi, nous avons montré récemment que la réalisation de seulement 23 échographies en présence d'un référent semblait nécessaire et suffisante pour l'apprentissage de la mesure échographique du col chez un novice [5].…”
Section: Le Toucher Vaginal : Examen Mensuel Dans Le Dépistage De L'aunclassified